Detecting opioid metabolites in exhaled breath condensate (EBC). (3rd October 2019) - Borras, Eva; Cheng, Andy; Wun, Ted; Reese, Kristen L; Frank, Matthias; Schivo, Michael; Davis, Cristina E
Abstract: Exhaled breath condensate (EBC) collection provides a promising matrix for bioanalysis of endogenous biomarkers of health and also for exogenous compounds like drugs. There is little information regarding drugs and their metabolites contained in breath, as well as their pharmacokinetics. In this present work, we use a simple and non-invasive technique to collect EBC from chronic pain patients using different analgesic opioid drugs to manage pain. Six patients received continuous infusion of morphine and hydromorphone intravenously (IV), together with other analgesic drugs (IV and orally). Repeated sampling of serum and EBC was done at two time points separated by 90 min. The EBC was collected using a glass tube surrounded by dry ice, and an ethanol solvent wash of the glass was performed after EBC extraction to retrieve the apolar compounds stuck to the glass surface. All samples were analyzed with liquid chromatography coupled to mass spectrometry (LC-MS/MS) to identify possible metabolites present in the sample, and to quantify the drugs being used. Several metabolites, such as normorphine (norM), norhydromorphone (norHM) and dihydromorphone (diHM) were detected in both fractions, while hydromorphone 3-glucuronide (HM 3G) was only detected in the solvent rinse fraction. Results were correlated to explain the pharmacokinetics of the main drugs administered. This pilot study presented promising correlations between drug concentrations in blood and breath at different time points for norM, norHM and HM 3G.